Decreased potassium fertilization in sugarcane ratoons grown under straw in different soils - de Almeida, Hilário Júnior [UNESP]; Cruz, Flávio José R. [UNESP]; Pancelli, Márcio Alexandre [UNESP]; Flores, Rilner Alves [UNESP]; Vasconcelos, Ricardo de Lima [UNESP]; Prado, Renato de Mello [UNESP] (My University, 2015)
The presence of straw from sugarcane (Saccharum ssp.) left on the soil surface after mechanical harvest has contributed to increase productivity of this crop and reduce potassium fertilization due to release of this nutrient and increased soil organic matter. Thus, the present study sought to evaluate the response of the second sugarcane ratoon cultivated under sugarcane straw resulting from harvest of the first ratoon, in function of potassium doses, in dystrophic Red Yellow Latosol (dRYL) and eutrophic Red Yellow Agirsol (eRYA). For this, two field experiments were conducted for the second sugarcane ratoon grown in the conservation system, where one experiment was developed in dRYL (variety SP81-3250) and the other in eRYA (variety RB855453). The treatments in both soil consisted of doses of 32.5, 65.0, 130.0 and 195.0 kg ha-1 of K2O in the form of potassium chloride, and a control treatment, arranged in a randomized block design with five repetitions. Potassium fertilizer was applied alongside the row of ratoons, without incorporation. We evaluated the biometric variables (height, tiller number and diameter), potassium contents in the soil, leaf and straw, K accumulation in the straw, stalk and shoot, production of straw and stalks, and technological quality. Potassium doses resulted in a productivity increase of about 75 and 22 Mg ha-1 in the dRYL and eRYA, respectively. The dose of 65 kg ha-1 of K2O, corresponding to 50% of the recommended dose for the conventional crop, promoted the acquisition of 88 and 95% of the maximum sugarcane crop yield in dRYL and eRYA, respectively. Potassium fertilization increases production and accumulation of this nutrient in sugarcane straw, potentially benefiting the upcoming crops.
Keywords: Mechanical harvest; Potassium chloride; Potassium fertilization; Saccharum spp; Technological quality